AZERBAIJAN IN EUROPEAN ENERGY SECURITY: NEW INITIATIVES AND PERSPECTIVES - Mirzayeva Kamala Kamal (Research Retrieval and Academic Letters, 2025)
One of the main reasons for Azerbaijan’s prominence in energy geopolitics is its rich energy resources, strong strategic position, and effective resource management. Azerbaijan’s energy wealth in the Caspian Sea increases its significance both in regional and global energy markets. The exploitation of oil and gas reserves has been carried out in international cooperation since the mid-1990s, forming the foundation of Azerbaijan’s energy policy. The State Oil Fund of Azerbaijan (SOFAZ), established for the management of Azerbaijan’s energy revenues, is aimed at diversifying the country’s economy, improving social welfare, and preserving wealth for future generations. This approach ensures the transparent and strategic use of resource revenues. At the same time, Azerbaijan’s energy infrastructure projects, particularly the Baku-Tbilisi-Ceyhan pipeline, strengthen the country’s energy position and deepen its relations with international partners. One of the important aspects of Azerbaijan’s energy policy is minimizing environmental impacts and applying a sustainable production model. These approaches aim to further develop Azerbaijan’s economy and increase its competitiveness in global energy markets. Azerbaijan’s independent and balanced approach in energy diplomacy contributes to strategic cooperation with regional countries and energy security in the global market. The primary goal of Azerbaijan’s energy diplomacy is to promote peace, ensure regional and global stability, and support long-term economic development. This also strengthens the country’s international position, helping it to be recognized as a reliable and strategic energy partner. One of the key reasons for Azerbaijan’s prominence in energy geopolitics is its rich natural resources, particularly oil and natural gas reserves. The fields located in Azerbaijan’s sector of the Caspian Sea give the country substantial energy potential, which holds strategic importance in both regional and global energy balance. Azerbaijan’s proven oil reserves are approximately 7 billion barrels, and its natural gas reserves are around 2.6 trillion cubic meters. The exploitation of these reserves has been carried out in international cooperation since the mid-1990s. The oil agreement signed in 1994, known as the "Contract of the Century," accelerated the flow of foreign investment into Azerbaijan’s energy sector. This agreement involved 11 foreign companies and was aimed at jointly developing the "Azeri-Chirag-Gunashli" (ACG) field in the Caspian Sea.